2010
DOI: 10.1007/s11627-010-9280-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple adventitious shoot formation in Spanish Red Cedar (Cedrela odorata L.) cultured in vitro using juvenile and mature tissues: an improved micropropagation protocol for a highly valuable tropical tree species

Abstract: Cedrela odorata L. is a valuable tropical tree widely appreciated for its wood. This species confronts serious problems due to both overexploitation of its natural populations and its susceptibility to the Meliaceae borer Hypsipyla grandella, which destroys the apical meristems and produces structural deformations. The rapid introduction of new varieties through clonal forestry has been demonstrated to be the most effective way to improve the production of perennial plantation species. In this work, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
(40 reference statements)
2
20
0
2
Order By: Relevance
“…We have previously reported on a protocol for C. odorata micropropagation in which hypocotyl segments were used as starting material and TY17 medium containing the plant growth regulator (PGR) dicamba was used as the induction culture medium (Gonzalez-Rodríguez and Peña-Ramírez 2007;Peña-Ramírez et al 2010). Using this protocol, we observed the induction of both adventitious shoot formation and the development of some proembryogenic calli.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on a protocol for C. odorata micropropagation in which hypocotyl segments were used as starting material and TY17 medium containing the plant growth regulator (PGR) dicamba was used as the induction culture medium (Gonzalez-Rodríguez and Peña-Ramírez 2007;Peña-Ramírez et al 2010). Using this protocol, we observed the induction of both adventitious shoot formation and the development of some proembryogenic calli.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the classes with longest shoots (5-6 cm, 6-7 cm, and higher than 7 cm), a higher regeneration was observed in TIS-TF. Similar results indicating the superiority of TIS for the production of shoots and plantlets with larger size were observed in peach palm (Steinmacher et al 2011), eucalyptus (McAlister et al 2005, Oliveira et al 2011), strawberry (Hanhineva et al 2005), Spanish red cedar (Peña-Ramíres et al 2010), lemon grass (Quiala et al 2006), sugarcane (Lorenzo et al 1998) and rubber tree (Etienne et al 1997). It was also observed that TIS-TF resulted in greater stability in the regeneration rate between different classes of shoot height.…”
Section: In Vitro Phase: Shoot Regenerationmentioning
confidence: 54%
“…Estos datos contrastan con los resultados obtenidos en este estudio ya que en T2 se obtuvieron plantas de 4.82 cm y 2.87 nudos en 5 semanas de cultivo. La literatura muestra también que la adición de 20% de agua de coco en el medio TY17 incrementa el número de brotes adventicios a partir de segmentos de hipocotilo de cedro con un número promedio de 4.68 brotes por explante ( Peña-González-Rodríguez & Peña-Ramirez, 2007;Ramírez et al, 2010). Asimismo trabajos realizados con Cedrela fissilis muestran que la adición de BAP al medio de cultivo es indispensable para la brotación y multiplicación de brotes axilares (Da Costa-Nunes et al, 2001).…”
Section: Resultados Y Discusiónunclassified